A case of Lennox‐Gastaut syndrome in a patient with FOXG1‐related disorder. Issue 11 (29th September 2014) - Terrone, Gaetano; Bienvenu, Thierry; Germanaud, David; Barthez‐Carpentier, Marie‐Anne; Diebold, Bertrand; Delanoe, Catherine; Passemard, Sandrine; Auvin, Stéphane
Summary Lennox‐Gastaut syndrome (LGS) is a drug‐resistant epileptic encephalopathy of childhood with a heterogeneous etiology. Recently, genome‐wide association studies have led to the identification of new de novo mutations associated with this epileptic syndrome. Herein, we report an 8‐year‐old child with intellectual disability, severe postnatal microcephaly, Rett‐like features, and LGS, carrying a de novo missense mutation in the forkhead box G1 (FOXG1) gene. This gene is responsible for FOXG1 syndrome, characterized by severe postnatal microcephaly, moderate postnatal growth deficiency, mental retardation with poor social interaction, stereotyped behavior and dyskinesias, absent language, sleep disorders, and epilepsy. Nonspecific epilepsy syndromes have been associated with this genetic disorder. Thus, we hypothesize that FOXG1 might be a new candidate gene in the etiology of LGS and suggest screening for this gene in cases of LGS with concomitant microcephaly and clinical features overlapping with Rett syndrome.